Analisis Hukum Mengenai Tindak Pidana Anak Yang Terlibat Geng Motor Sebagai Upaya Penegakan Hukum - Kaston Rudy Samosir; Ediwarman Ediwarman; Taufik Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This article or article aims to examine and analyze the legal rules governing children involved in motorcycle gangs, as well as the factors causing criminal acts against children involved in motorcycle gangs, as well as legal policies carried out by the police against children involved in motorcycle gangs. The problem is focused on how the legal rules regulate children who are involved in motorcycle gangs. In order to approach this problem, the reference theory of law enforcement, theory of legal certainty and theory of policy is used. The research method in this paper is a normative legal research method. The data were collected through primary, secondary and tertiary data sources, then analyzed using qualitative analysis methods. This study concludes that the legal rules regarding children involved in motorcycle gangs are contained in: the 1945 Constitution of the Republic of Indonesia, Law Number 1 of 1946 concerning the Criminal Code, Law Number 1 of 1974 concerning Marriage, Law Number 4 1979 concerning Child Welfare, Law Number 3 of 1997 concerning Juvenile Court, Law Number 23 of 2002 concerning Child Protection, Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Factors that cause crime against children involved in motorcycle gangs are as follows: (1) family factors, (2) social environment factors, (3) education factors. The legal policies carried out by the police against children involved in motorcycle gangs are as follows: (1) Penal policies are applied to children involved in motorcycle gangs as well as non-penal policies.